The hydrogeological potential of Doma Rutu Floodplains for shallow groundwater irrigation: a technical report - Oke, Adebayo; Igbadun, H.; Adeogun, B.; Tilahun, Seifu A.; Atampugre, Gerald; Cofie, Olufunke O. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2024)
A situation analysis was conducted to increase food production, build small-scale farmers’ resilience to climate change, and improve livelihood in the Doma-Rutu socioecological landscape. An Inclusive Landscape Management Plan (ILMP) was then developed with inputs from the situation analysis and various engagements with identified stakeholders in the landscape. One of the shared goals and activities in the ILMP was to build farmers' capacity to develop additional water resources and manage them to improve their agricultural production during the dry season. The use of shallow tube wells was identified as a proven innovation that could transform the landscape by exploring groundwater for irrigation. However, knowledge gaps exist on the hydrogeology of the floodplains, especially information about the water table depths at the peak of the dry season and whether shallow tube wells are feasible and can sustainably support sufficient water for irrigation purposes. To address this gap, a hydrogeological survey was carried out in two selected floodplains in the landscape. The floodplain surveyed in Iwashi was about 118ha, and that of Alagye was about 90 ha. The study revealed that the floodplains had deposits of alluvial materials such as sands, clays, and silty materials. These were products of weathered basement and sedimentary rocks from uplands and surrounding areas adjacent to the river courses. The investigation reflected that Iwashi geologic formations were sedimentary, while very few locations in Alagye had basement complex formations. The alluvial materials are saturated and can be harnessed for dry-season irrigation farming. The study also showed that the floodplains could contribute to groundwater flow, subsurface flow to the stream, and the normal channel flow. Moreover, the floodplains could for excess water during the rainy season. The depth of tube wells for the Iwashi floodplain will range from 8.6 to 14 m and from 9.5 to 14m for the Alagye floodplain. It is recommended that very fine materials be used as gravel packing during the construction of the tube wells because most of the alluvial aquifers are fine sand in nature and can easily get deposited into the tube wells if the gravel materials around the tube well are not wellselected. Each tube well should be installed so that about 5 to 6 meters of the bottom part are screened to allow sufficient inflow of groundwater. The is to increase the surface area for water inflow into the tube-well. An optimal selection of pumps is necessary, which can be determined by a pumping test. The result of the pumping test will aid in determining the command area in which each tube well can irrigate optimally. This survey has further established the prospect for shallow groundwater irrigation using the tubewell innovation, which is a proven technology in use in the states of Kano, Kebbi, Niger, Bauchi, and some other states in Nigeria. Tubewell technologies are cost-effective and simple in floodplains where the geological formation, aquifer is shallow and feasible.